Chronic Kidney Disease Related to Cognitive Disorders in the Elderly: A Narrative Literature Review - Ajat Sudrajat; Drajad Priyono; Harnavi Harun; Roza Kurniati; Roza Mulyana (HM Publisher, 2022)
Chronic kidney disease (CKD) is characterized by progressive and irreversible kidney damage, leading to the inability of the kidneys to perform their functions. Chronic kidney disease causes hypertension, anemia, vascular dysfunction, uremia, proteinuria, systemic inflammation, and oxidative stress associated with cognitive impairment. Age is a population group aged 60 years or more at risk of experiencing health problems and the consequences associated with CKD. One of the common comorbidities experienced by elderly patients with CKD is cognitive impairment. Current treatment options for CKD with cognitive impairment aimed at common risk factors, including angiotensin converting enzyme inhibitors (ACEI) and, angiotensin receptor blockers (ARBs), SGLT-2 inhibitors., GLP-1 RA, and DPP-4 inhibitors. Other interventions, such as erythropoietin (EPO) compensation and reduction of inflammation and oxidative stress, can help improve patients' clinical symptoms. This literature review aims to describe the relationship between chronic kidney disease and cognitive disorders that occur in the elderly.